2016
DOI: 10.1002/em.21998
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposure to second‐hand smoke activates pro‐asthmatic and oncogenic miRNAs in adult asthmatic mice

Abstract: Exposures to environmental pollutants contribute to dysregulated microRNA (miRNA) expression profiles, which have been implicated in various diseases. Previously, we reported aggravated asthmatic responses in ovalbumin (OVA)‐challenged adult mice that had been exposed in utero to second‐hand smoke (SHS). Whether in utero SHS exposure dysregulates miRNA expression patterns in the adult asthma model has not been investigated. Pregnant BALB/c mice were exposed (days 6–19 of pregnancy) to SHS (10 mg/m3) or HEPA‐fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…As mentioned previously, it is well known that both types of alteration are associated with tumor formation, with hypomethylation status being associated with activation of oncogenes and hypermethylation with silencing of tumor suppressors [40]. Thus, in addition to our results, there is increasing evidence for epigenetic effects of in utero SHS exposure alone on lung development with persistence into adult life, and this may predispose to respiratory morbidity, including lung cancer [39]. …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As mentioned previously, it is well known that both types of alteration are associated with tumor formation, with hypomethylation status being associated with activation of oncogenes and hypermethylation with silencing of tumor suppressors [40]. Thus, in addition to our results, there is increasing evidence for epigenetic effects of in utero SHS exposure alone on lung development with persistence into adult life, and this may predispose to respiratory morbidity, including lung cancer [39]. …”
Section: Discussionsupporting
confidence: 76%
“…SHS is a major indoor air pollutant and increasing numbers of epidemiological and experimental studies have associated in utero exposure to SHS with adverse outcomes in newborns [2, 23, 25, 3739]. Here we investigated whether in utero SHS exposure alone is sufficient to alter lung structure and function in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have investigated the long-term effects of in utero SHS exposure (16)(17)(18)54), a limited number of studies have explored the short-term effects of neonatal SHS exposure. Given the highly sensitive stage of ongoing lung development, the superimposition of exposure to SHS or any other airborne environmental pollutant upon early postnatal life makes interpretation of these studies challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of miR-92a-3p modified the transcription of KAT2B and PARP1, which played an important role in the development of combined allergic rhinitis and asthma syndrome [26]. Xiao et al reported that miR-155 participated in immune regulation by setting a balance between Th1 and Th2 responses, and the expression level of miR-155-5p was highly related to protein expression of the pro-asthmatic Th2 cytokines in bronchoalveolar lavage fluid (BALF) samples [27]. A study of sputum showed miR-223-3p was significantly upregulated in sputum of patients with severe asthma, and was highest in neutrophilic asthma, the expression was also associated with airway obstruction (FEV1/ forced vital capacity) [28].…”
Section: Literature Validation Of Rnas In Key Lncrnas Related Cerna Smentioning
confidence: 99%